Advanced Computational Methods and Experiments in Heat Transfer XII 2012
DOI: 10.2495/ht120061
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of solar chimney integrated with exhaust of thermal power plant

Abstract: The heat losses within exhaust gases are an unavoidable part of operating any fuel-fired system. The flue gases still hold considerable thermal energy, which is exhausted to the atmosphere as waste heat and contributes to global warming. This paper presents a developed technique to enhance the performance of low temperature solar thermal systems by utilization of thermal energy recovery of flue gases. A CFD model was established based on the energy, momentum and mass conservation and the state equation in 2-D,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…AlMustafa et al [2] reported review of the enhancement of the solar power updraft systems. Al-Kayiem [3] and Al-Kayiem et al [4] presented experimental and numerical results of modified SCPP integrated with external auxiliary thermal source. They concluded that considerable enhancement was achieved in the performance of the integrated system and the SCPP became able to produce electricity all the day and night due to the continuous heat supply to the absorber.…”
Section: Introductionmentioning
confidence: 99%
“…AlMustafa et al [2] reported review of the enhancement of the solar power updraft systems. Al-Kayiem [3] and Al-Kayiem et al [4] presented experimental and numerical results of modified SCPP integrated with external auxiliary thermal source. They concluded that considerable enhancement was achieved in the performance of the integrated system and the SCPP became able to produce electricity all the day and night due to the continuous heat supply to the absorber.…”
Section: Introductionmentioning
confidence: 99%
“…Elementary experimental measurements on an inclined solar chimney model integrated with flue gas were reported by Al-Kayiem et al [26]. Then, the same system was simulated and the simulation results were validated through comparison with the measurement results as reported by Al-Kayiem et al [27]. The experimental and simulation boundary conditions are shown in Fig.…”
Section: Hybrid Solar-flue Chimney Power Plantmentioning
confidence: 97%
“…Chikere et al [4] reviewed the enhancement of the SCPP and suggested a modified SCPP integrated with flue gas as a supplementary source of heat. Al-Kayiem et al [5] and Al-Kayiem [6] presented the experimental and numerical results of a modified SCPP integrated with an external auxiliary thermal source. They concluded that considerable enhancement was achieved in the performance of the integrated system, and the SCPP was able to produce electricity during daytime and night time because of the continuous heat supply to the absorber.…”
Section: Introductionmentioning
confidence: 99%